2021
DOI: 10.1111/exd.14302
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90 inhibitor RGRN‐305 exhibits strong immunomodulatory effects in human keratinocytes

Abstract: Keratinocytes are the key cellular target for IL‐17A‐mediated effects in psoriasis and HSP90 is important for IL‐17A‐mediated signalling. RGRN‐305 is a novel HSP90 inhibitor reported to reduce psoriatic phenotypes in preclinical animal models. The aim of this study was to investigate the effect of RGRN‐305 on a psoriasis‐like inflammatory response in human keratinocytes in vitro. Using RT‐qPCR, we demonstrated a significantly increased expression of the HSP90 isoforms HSP90AB1, HSP90B1 and TRAP1 in lesional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…43 This inactivation of HSP90 leads to inhibition of the expression of multiple proinflammatory cytokines and chemokines, as recently shown in cultured normal human keratinocytes in vitro, where cells stimulated with either IL-17A and TNF-a or the Toll-like receptor 3 agonist poly(I:C) showed reduced expression of a number of proinflammatory genes such as CCL20, IL36G, IL23A, TNF-a, IL1B and IL6. 18 This is consistent with findings from the present study where treatment with RGRN-305 normalized the gene expression signature in psoriasis lesions in the responder group over the 12week treatment period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…43 This inactivation of HSP90 leads to inhibition of the expression of multiple proinflammatory cytokines and chemokines, as recently shown in cultured normal human keratinocytes in vitro, where cells stimulated with either IL-17A and TNF-a or the Toll-like receptor 3 agonist poly(I:C) showed reduced expression of a number of proinflammatory genes such as CCL20, IL36G, IL23A, TNF-a, IL1B and IL6. 18 This is consistent with findings from the present study where treatment with RGRN-305 normalized the gene expression signature in psoriasis lesions in the responder group over the 12week treatment period.…”
Section: Discussionsupporting
confidence: 92%
“…[15][16][17] HSP90 is also known as a downstream regulator of IL-17A signalling. 14,18 Human psoriatic lesions display increased expression of HSP90 compared with nonlesional skin and normal skin, which is thought to be partially associated with IL-17-induced inflammation. 16,19 In addition, HSP90 is also employed in Janus kinase/signal transduction and activator of transcription (JAK/ STAT) signalling.…”
mentioning
confidence: 99%
“…The HSP90 inhibitor RGRN-305 has shown promising antipsoriatic effects in a xenograft mouse model, and in vitro it inhibited the expression of proinflammatory genes such as TNFα, IL23A and NFKBIZ (encoding IκBζ) in cultured normal human keratinocytes. 125 , 126 A Phase 1 clinical trial with RGRN-305 in patients with psoriasis is currently ongoing (NCT03675542).…”
Section: Treatmentmentioning
confidence: 99%
“…In the current issue, Hansen et al 11 . found that RGRN‐305, a novel HSP90 inhibitor, potently suppress TNF, IL‐17A and/or poly(I:C)‐mediated proinflammatory responses in cultured keratinocytes.…”
Section: Potential Endogenous Anti‐inflammatory Moleculesmentioning
confidence: 89%
“…We also include new EXD studies related to allergic contact dermatitis (ACD), because it shares similar signs and symptoms as AD, including pruritus, along with burning and stinging 8 . In this Editorial, these recent EXD papers are briefly highlighted and placed into the context of the current literature, including four articles in the current issue 9‐12 . With this exercise, the Editors hope to synthesize exemplarily where translational immunopathology research in these key areas of experimental dermatology is headed, and which challenges and open questions remain.…”
mentioning
confidence: 99%